Emerging infectious diseases - Stavrakakis, P.; Chalaris, Michail; Stamataki, Petroula; Zyga, Sofia; Saroglou, George J.; Sarafis, Pavlos (My University, 2010)
The field of infectious disease is vast, complex and rapidly expanding. New advances in diagnostic testing, the development of new antimicrobial therapies and even the emergence of novel infectious diseases require diligent study by medical practitioners to remain current. International travelling can pose various risks to health, depending on the characteristics of both the traveller and the travel. Travellers may encounter sudden and significant changes in altitude, humidity, microbes and temperature, which can result in ill-health. In addition, serious health risks may arise in areas where accommodation is of poor quality, hygiene and sanitation are inadequate, medical services are not well developed and clean water is unavailable. The purpose of this paper is to highlight the details and impact of 4 significant diseases that pose a threat to public health. Specifically issues are such as the cause, transmission, geographical distribution, nature of disease and precautions of SARS, influenza, chikungunya and avian flu.
Keywords: Εmerging infectious diseases; SARS; Influenza; Chikungunya; Avian flu; Travel medicine; Tropical diseases